Globalization and Firm Competitiveness in the Middle East and North Africa Region - Fawzy, Samiha (Washington, DC: World Bank, 2013)
Globalization has increased competitive pressures on firms. Together with rapid technological change, it has altered the environment in which firms operate. While globalization offers unprecedented opportunities for firms to act successfully, it simultaneously heightens the risks for firms lagging behind. In an open and liberalized world, increasing firm competitiveness has become a major challenge. This book provides a thorough analysis of the competitiveness of firms in the Middle East and North Africa Region (MENA). It is organized into four parts which detail the different issues related to firm competitiveness from global rules for business, regional business environment, corporate governance, and the key economic sectors of small/medium size enterprises, and tourism. In addition, the book also addresses key issues for the future of the region including the real challenges facing firms' operations and efficiency, the ability of MENA firms to compete in global markets, the impact of small, and medium size enterprises on the stimulation of growth, and the economic potential of the tourism sector.